Gifted education in the United States: Perspectives of gender equity - Pierson, Melinda R. (Wydawnictwo Naukowe UAM, 2014)
An overview of education for gifted and talented children and adolescents in the United States will be presented. Issues of gender equity will be discussed and suggestions for creating equal opportunities for all students will be outlined.
Keywords: gender equity; gifted education; equal opportunity